ANALISIS MANAJEMEN KEARSIPAN DI KANTOR KECAMATAN JAGAKARSA KOTA ADMINISTRASI JAKARTA SELATAN - Yuniasih Yuniasih; Bambang Irawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
The phenomenon that made the object of writing is the management of archives in the Office of District Jagakarsa City Administration South Jakarta is still problematic in its management. The purpose of writing is (1) To explain the implementation of archival management (2) To determine the factors inhibiting the implementation of archival management (3) To know the efforts and follow-up in archives management Jagakarsa District Office. Writing method used is descriptive qualitative method. The data collection was done by bibliography study and interview guide. Determination of informant writing as much as 5 informant writing. Analysis of archives management indicators at Jagakarsa Sub-district Office are 8 (eight) indicators, namely: recording, controlling, distribution, storage, maintenance, monitoring, transfer and destruction.Based on the discussion of the results obtained the conclusion, namely: (1) Archives management in the Office District Jagakarsa South Jakarta Administration has not run optimally and well. This can be seen from the recording process that is still using the agenda book, not yet computerized; Control processes that are not yet optimal; the distribution process that still uses the disposition sheet so it has not gone well; Maintenance process not implemented; (2) Obstacles encountered in the management of archives at the Jagakarsa District Office of South Jakarta Municipality are the means and infrastructure are not yet available, the budget is still very low, human resources are not yet competent in the management of the archives; (3) The efforts undertaken to deal with the constraints found in the management of archive management in sub-district jagakarsa is the communication between the managerial areas not yet one door managing the archives properly and correctly so that it needs to be made one door management of the archive management and if necessary appointed special officials who handle the archives at the Jagakarsa Sub-district Office.